Epipleoneura angeloi (Odonata: Protoneuridae), a new species from the central region of Brazil - Pessacq, Pablo (2010)
Epipleoneura angeloi sp. nov., is described and illustrated based on males from Mato Grosso and Goiás states, central region of Brazil.